Modeling and Synthesis of Ag and Ag/Ni Allied Bimetallic Nanoparticles by Green Method: Optical and Biological Properties - Anuoluwa Abimbola Akinsiku (International Journal of Biomaterials, 2018)
In the quest for environmental remediation which involves eco-friendly synthetic routes, we herein report synthesis and modeling of silver nanoparticles (Ag NPs) and silver/nickel allied bimetallic nanoparticles (Ag/Ni NPs) using plant-extract reduction method. Secondary metabolites in the leaf extract of Canna indica acted as reducing agent. Electronic transitions resulted in emergence of surface plasmon resonance in the regions of 416 nm (Ag NPs) and 421 nm (Ag/Ni NPs) during optical measurements. Further characterizations were done using TEM and EDX. Antimicrobial activity of the nanoparticles against clinical isolates was highly significant as P<0.05. These findings suggest application of Ag NPs as antibacterial agent against E. coli, S. pyogenes, and antifungal agent against C. albicans. Possible antibacterial drugs against S. pyogenes and E. coli can also be designed using Ag/Ni nanohybrid based on their strong inhibition activities. Similarly, the enhanced SPR in the nanoparticles is suggested for applications in optical materials, as good absorbers and scatters of visible light. Theoretical model clarified that the experiment observation on the relationship between metallic nanoparticles penetration through peptidoglycan layers and the activeness of microbial species depends on the nature of the nanoparticles and pore size of the layer.